Chapter 5 Miljøets betydning i elitesport - Hvid Larsen, Carsten (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"In recent years there has been an increased focus on the importance of the environment for the development of elite athletes. In order to understand the factors that contribute to or limit an athlete's sporting development, it is not enough to study only the individual but the whole environment in which the athlete develops. The purpose of this chapter is to investigate what characterizes a successful elite sport environment in Danish badminton. An elite sports environment that continuously manages to create senior results at the highest international level and win medals at the European championships, the World championships and the Olympics. The study was organized as a case study of the national elite sports center in Badminton Denmark (BD). Data was based on interviews with players, coaches and managers, observations on training and in competitions, meetings and analysis of documents. The environment was centered on self-understanding based on "us against the rest of the world" and a fundamental value in the environment was to create intelligent players while focusing on individual development through high training quality. The organizational culture was characterized by being: 1) a well documented, quality oriented and dialogue-based learning environment, 2) an environment with hard competition and 3) an environment with proximal role models."